Durvalumab-induced myocarditis, myositis, and myasthenia gravis: a case report - Cham, Jason (J Med Case Rep, 2021)
BACKGROUND: Immune checkpoint inhibitors are effective therapies for a wide range of malignancies. Their increased use has led to a wide range of immune-related adverse effects including skin, gastrointestinal, pulmonary, endocrine, cardiac, and neurologic complications. CASE PRESENTATION: We present the case of a 72-year-old Caucasian man with non-small cell lung cancer who was admitted for dyspnea after two cycles of durvalumab. He was found to have significantly elevated levels of serum creatinine kinase and troponin with a negative cardiac catheterization. During his hospitalization, he developed progressive dyspnea and new-onset axial weakness, ultimately leading to the diagnosis of durvalumab-induced myocarditis, myasthenia gravis, and myositis. CONCLUSION: This is, to our knowledge, the first reported case of anti-programmed cell death ligand 1-induced combination of myocarditis, myasthenia gravis, and myositis. While the use of immunologic agents has resulted in overall improved cancer outcomes, their increased use has led to a vast spectrum of immune-related adverse effects. We review the diagnostic workup and management of patients with these immune-related adverse effects, underscoring the importance of early identification given the potential for rapid deterioration.